Identification of volatile compounds associated with the aroma of white strawberries (Fragaria chiloensis). (21st October 2013) - Prat, Loreto; Espinoza, María Inés; Agosin, Eduardo; Silva, Herman
Abstract BACKGROUND Fragaria chiloensis (L.) Mill spp. chiloensis form chiloensis, is a strawberry that produces white fruits with unique aromas. This species, endemic to Chile, is one of the progenitors of Fragaria x ananassa Duch. In order to identify the volatile compounds that might be responsible for aroma, these were extracted, and analyzed by gas chromatography–mass spectrometry (GC‐MS), gas chromatography–olfactometry (GC‐O) and compared with sensory analyses. RESULTS Three methods of extraction were used: solvent‐assisted evaporation (SAFE), headspace solid phase micro‐extraction (HS‐SPME) and liquid–liquid extraction (LLE). Ninety‐nine volatile compounds were identified by GC‐MS, of which 75 showed odor activity using GC‐O. Based on the highest dilution factor (FD = 1000) and GC‐O intensity ≥2, we determined 20 major compounds in white strawberry fruit that contribute to its aroma. We chose 51 compounds to be tested against their commercial standards. The identities were confirmed by comparison of their linear retention indices against the commercial standards. The aroma of white strawberry fruits was reconstituted with a synthetic mixture of most of these compounds. CONCLUSION The volatile profile of white strawberry fruit described as fruity, green–fresh, floral, caramel, sweet, nutty and woody will be a useful reference for future strawberry breeding programs. © 2013 Society of Chemical Industry